PROGNOSIS IN PATIENTS WITH ST SEGMENT ELEVATION MYOCARDIAL INFARCTION, IN REGARD TO THE PRESENCE OF TYPE 2 DIABETES MELLITUS AND SELECTED TREATMENT STRATEGY IN THE ACUTE PERIOD - Yu. A. Belen’kova; E. V. Tavlueva; V. N. Karetnikova; M. V. Zykov; V. V. Kashtalap; V. N. Ganyukov; O. L. Barbarash (Российский кардиологический журнал)
Aim. To assess the results of endovascular revascularisation in patients with acute myocardial infarction (AMI) and ST segment elevation (STEMI), in regard to the presence of Type 2 diabetes mellitus (DM-2), in the real-world clinical settings. Material and methods. The study included 423 STEMI patients, with or without concomitant DM-2. In the DM-2 group (n=77, 18,20%), percutaneous coronary intervention (PCI) was performed in 35 individuals (45,5%); in participants without DM-2, the respective figure was 54,91% (n=190). The follow-up period lasted for one year. The adverse long-term prognosis included repeated non-fatal MI and/or stroke, cardiac death, unstable angina, and decompensated heart failure (combined end-point). Results. In patients who underwent PCI, the presence of DM-2 did not affect substantially (p>0,05) the incidence of adverse clinical outcomes: it reached 28,57% (n=10) in participants with STEMI and DM-2 and 30,53% (n=58) in STEMI patients without DM-2. However, among individuals who did not undergo PCI, DM-2 was associated with increased incidence of the combined end-point: 52,38% (n=22) among those with STEMI and DM-2 vs. 42,95% (n=67) among those with STEMI only. Repeated interventions due to stent thrombosis (n=2; 5,71%) or stent restenosis (n=4; 11,43%) were non-significantly more frequent among patients with DM-2, compared to the non-diabetic patients (1,05% (n=2) and 3,68% (n=7), respectively). Therefore, PCI in STEMI patients with DM-2 substantially improved the long-term prognosis, halving the incidence of the combined end-point. By contrast, this incidence was reduced only by 1,5 among patients who did not undergo PCI. To summarise, the presence of DM-2 is associated with adverse long-term prognosis only in STEMI patients who do not undergo PCI. Conclusion. The presence of DM-2 significantly aggravates long-term prognosis in AMI patients who do not undergo PCI.